Mitochondrial Genomes from Fungal the Entomopathogenic Moelleriella Genus Reveals Evolutionary History, Intron Dynamics and Phylogeny - Chengjie Xiong; Yongsheng Lin; Nemat O. Keyhani; Junya Shang; Yuchen Mao; Jiao Yang; Minghai Zheng; Lixia Yang; Huili Pu; Longbing Lin; Taichang Mu; Mengjia Zhu; et al. (Journal of Fungi, 2025)
Members of the genus Moelleriella (Hypocreales, Clavicipitaceae) are insect pathogens with specificity for scale insects and whiteflies. However, no mitochondrial genomes are available for these fungi. Here, we assembled seven mitogenomes from M. zhongdongii, M. libera, M. raciborskii, M. gracilispora, M. oxystoma, Moelleriella sp. CGMCC 3.18909, and Moelleriella sp. CGMCC 3.18913, which varied in size from 40.8 to 95.7 Kb. Synteny and codon usage bias was relatively conserved, with the mitochondrial gene arrangement being completely homologous to the gene order of 21 other species within the Hypocreales. Nevertheless, significant intron polymorphism was observed between Moelleriella species. Evolutionary analyses revealed that all 15 core protein–coding genes had ka/ks < 1, indicating purifying selection pressure. Sequence variation within the mitochondrial ATP synthase F0 subunit 6 (atp6) gene showed the largest genetic distance, with the ATP synthase F0 subunit 9 (atp9) gene showing the smallest. Comparative analyses of mitogenomes revealed that introns were the primary factor contributing to the size variation in Moelleriella and, more broadly, within Hypocreales mitogenomes. Phylogenetic analyses indicated that the seven Moelleriella species examined form a well–supported clade, most closely related to Metarhizium. These data present the first mitogenomes from Moelleriella and further advance research into the taxonomy, origin, evolution, and genomics of Moelleriella.